2010
DOI: 10.1177/1082013210379688
|View full text |Cite
|
Sign up to set email alerts
|

Review. Sulfur-containing Volatile Compounds in Seafood: Occurrence, Odorant Properties and Mechanisms of Formation

Abstract: An inventory of the most part of sulfur-containing volatile compounds (SCVCs) present in seafood was carried out. These molecules constitute key compounds to understand and improve seafood quality. According to their nature, concentration and environmental parameters (temperature), they can move the overall seafood odor from desirable to rotten. Sulfury odors can also indicate problems in sanitary quality. Thus, it is essential to monitor the generation of these compounds to better control the organoleptic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 197 publications
(263 reference statements)
1
40
0
2
Order By: Relevance
“…Varlet and Fernandez (2010) reviewed the occurrence, odorant properties and formation mechanisms of sulfur-containing volatile compounds in seafood. MeSH, DMS and DMDS were important components of seafood odour while DMTS was a marker of spoilage (Duflos et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Varlet and Fernandez (2010) reviewed the occurrence, odorant properties and formation mechanisms of sulfur-containing volatile compounds in seafood. MeSH, DMS and DMDS were important components of seafood odour while DMTS was a marker of spoilage (Duflos et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The kinetics of the acute release of aromas from food or beverages is complex, being dependent on the physiological processes involved in swallowing, the lipid content of the food ( 36 ) and the vapour pressure of the compound ( 37 ) . There are a number of volatile compounds in food that may rapidly appear in the breath following their consumption ( 38 40 ) .…”
Section: Physiological Variations In Breath Compositionmentioning
confidence: 99%
“…Thioamides, herein present in shrimp, have also been reported for crab (Chung, 1999) and dried squid (Kawai et al, 1991). Thiazoles, have been found in cuttlefish oil (Shen et al, 2007) and cooked squid (Kubota et al, 1996) and have been reported as heating products in seafood (Varlet & Fernandez, 2010).…”
Section: Resultsmentioning
confidence: 76%
“…The S-containing compounds, are considered to be enzymatically produced in seafood from methionine and cysteine (Varlet & Fernandez, 2010). Thioamides, herein present in shrimp, have also been reported for crab (Chung, 1999) and dried squid (Kawai et al, 1991).…”
Section: Resultsmentioning
confidence: 91%